Cash Waqf for Public Health Expenditure - NOR, NOR AKMAR MOHD; SARIB, NORHANIM MAT (International Journal of Islamic Economics and Governance, 2023)
Recently, the COVID-19 pandemic and economic crisis have imposed constraints on government spending and increased borrowing to redevelop the economy. Thus, there is a need for alternative funding sources to ease the government’s financial burden. Cash waqf has the potential to finance public health sector expenditures. Additionally, giving behavior plays a significant role in establishing cash waqf funds and ensuring the sustainability of waqf institutions. This paper examines the views of the public, specifically Muslims in the Klang Valley, Malaysia, regarding cash waqf and their willingness to contribute to it as an alternative financing method for public healthcare expenditures. The research framework combines variables from the Theory of Planned Behavior (TPB) and additional variables such as attitude, perceived behavioral control, religiosity, and trust in waqf institutions. The study finds that Muslims in the Klang Valley are aware of and willing to contribute to cash waqf for public health expenditure, especially during the COVID-19 pandemic. The study further reveals that attitude and perceived behavioral control are significant factors influencing their intention to contribute. These findings can encourage relevant authorities to consider cash waqf as an alternative financing source for public health expenditures, benefiting both Muslims and non-Muslims.